In vitro models of the choroid plexus and the blood-cerebrospinal fluid barrier: advances, applications, and perspectives - Schwerk, Christian; Schroten, Horst (Human cell, 2024)
The choroid plexus (CP), a highly vascularized endothelial-epithelial convolute, is placed in the ventricular system of the brain and produces a large part of the cerebrospinal fluid (CSF). Additionally, the CP is the location of a blood-CSF barrier (BCSFB) that separates the CSF from the blood stream in the CP endothelium. In vitro models of the CP and the BCSFB are of high importance to investigate the biological functions of the CP and the BCSFB. Since the CP is involved in several serious diseases, these in vitro models promise help in researching the processes contributing to the diseases and during the development of treatment options. In this review, we provide an overview on the available models and the advances that have been made toward more sophisticated and “in vivo near” systems as organoids and microfluidic lab-on-a-chip approaches. We go into the applications and research objectives for which the various modeling systems can be used and discuss the possible future prospects and perspectives.